Tufted Puffin (Fratercula cirrhata) 3dRADseq and msat data - Burg, Theresa; Graham, Brendan (Zenodo, 2023)
The tufted puffin ( Fratercula cirrhata ) is a medium sized seabird found throughout the North Pacific Ocean. Although populations of tufted puffins appear to be stable or increasing in some parts of their distribution, they are experiencing significant declines in other parts of their distribution, including in the Gulf of Alaska. Assessments of tufted puffin population status in Alaska are currently limited because little is known about population genetic structure. Similarly, there is little information on the amount of dispersal between populations in Alaska, and between populations in Alaska and those in the southern portion of the species' range. If genetic analyses reveal significant genetic differentiation between tufted puffins nesting in different regions of Alaska, or evidence of local adaptation, then the apparent decline in the Gulf of Alaska becomes more of a conservation concern. There is general consensus within the tufted puffin research and management community that a study of population genetic structure is a high priority. As part of our ongoing research, we conducted genetic analysis to determine if tufted puffin nesting colonies form single or multiple conservation units, and populations show evidence of local adaptation, using traditional population genetic analysis and next-generation sequencing techniques. Continuing analyses of genome-wide associations between environment and genetic adaptation for tufted puffins will also provide greater insight into how coastal seabird populations in the temperate North Pacific Ocean are coping with the effects of climate change. Funding provided by: U.S. Fish and Wildlife Service Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000202 Award Number: F21AP02488 Funding provided by: Environment and Climate Change Canada Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100008638 Award Number: